2017
DOI: 10.1111/petr.13038
|View full text |Cite
|
Sign up to set email alerts
|

Safety of hematopoietic cell infusion in children with malignant and non‐malignant diseases

Abstract: HPC infusions have been associated with a variety of adverse events related to either patient or HPC product-related factors. Studies documenting infusion-related AEs in children are limited. We reviewed HPC infusion records in 354 children. Infusion-related adverse events were classified as follows: grade 0-absent, grade I-mild, grade II-moderate, grade III-severe, grade IV-life-threatening, and grade V-death. The percentage of patients with grade 0, I, and II-IV AEs was as follows: 0 = 67%, I = 23.4%, and II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Although HCI-AEs were most frequently noted in BMT in a recent retrospective study of pediatric recipients, a vast majority of the HCI-AEs in their study was hypertension in BMT. 15 Consistent with this, the present study found hypertension was the most frequent HCI-AE, especially in BMT, in pediatric recipients and small adult recipients. However, our study also detected several HCI-AEs other than hypertension, which might have led to a comparable overall HCI-AE incidence in BMT compared with other sources.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Although HCI-AEs were most frequently noted in BMT in a recent retrospective study of pediatric recipients, a vast majority of the HCI-AEs in their study was hypertension in BMT. 15 Consistent with this, the present study found hypertension was the most frequent HCI-AE, especially in BMT, in pediatric recipients and small adult recipients. However, our study also detected several HCI-AEs other than hypertension, which might have led to a comparable overall HCI-AE incidence in BMT compared with other sources.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it has also been reported that gastrointestinal symptoms, including nausea and vomiting, were often observed in pediatric recipients who were infused with HSC products. 15,16 Although it might be conceivable that the fast infusion contributed to such symptoms, the rate of infusion in pediatric recipients with nausea and vomiting was very similar to those without the symptoms (not shown). Also, antiemetics were prophylactically used in some pediatric recipients, but the administration of antiemetics did not reduce the incidence of gastrointestinal symptoms in our limited data.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations